Happiness at Work and Work Engagement Affecting the Performance Effectiveness of the Personnel of the Administrative Organizations in Mueang Sakon Nakhon District, Sakon Nakhon Province - Katbumrung, Preeyanuch; Udomkijmongkol , Chardchai; Aiyakorn, Samart (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: At present, both public and private organizations are giving importance to promoting personal happiness at work. The reason that personnel are happy at work is an important thing that will bring success to the organization in the future. This is because employees who are happy with their work will be more engaged and will work more efficiently. Thus, the purposes of this research included the following: 1) To study the level of happiness at work, work engagement, and the performance effectiveness of the personnel of the administrative organizations in Mueang Sakon Nakhon District. 2) To investigate the influences of happiness at work and work engagement on the performance effectiveness of the personnel of the administrative organizations in Mueang Sakon Nakhon District. Methodology: it was obtained through a stratified random sampling method, the samples were composed of 268 personnel who reported to the administrative organizations in Mueang Sakon Nakhon District, Sakon Nakhon Province. The questionnaire was used as the tool for data collection and statistics employed for data analysis incorporated frequency, percentage, standard deviation, and Multiple Regression Analysis. Results: (1) The happiness at work of the personnel of the administrative organizations in Mueang Sakon Nakhon District, as a whole, was at a high level. Likewise, the work engagement of the personnel of the administrative organizations in Mueang Sakon Nakhon District, as a whole, was at a high level as well. In a similar vein, the overall performance effectiveness of the personnel of the administrative organizations in Mueang Sakon Nakhon District was at a high level. (2) In light of happiness at work, these aspects significantly influenced the performance effectiveness of the personnel of the administrative organizations in Mueang Sakon Nakhon District, at .01 statistical level: success in work (β=.415), love to work (β=.218), acceptance/recognition in the workplace (β=.201), communication and relationships (β=.127). Altogether, these aspects could be used to correctly predict the level of performance effectiveness of the personnel of the administrative organizations in Mueang Sakon Nakhon District, 77.10 percent (R2Adj=.771). Regarding work engagement, these aspects significantly influenced on the performance effectiveness of the personnel of the administrative organizations in Mueang Sakon Nakhon District, at .01 statistical level: commitment/dedication to work (β =.705) and work absorption/identification with work (β =.327). Although these aspects could be used jointly for the prediction of the performance effectiveness level of the personnel of the administrative organizations in Mueang Sakon Nakhon District, 79.60 percent (R2Adj=.796), diligence did not show any influence on the performance effectiveness of these personnel. Conclusion: The study affirms a strong positive correlation between happiness at work, work engagement, and overall performance effectiveness among administrative personnel in Mueang Sakon Nakhon District. Specific factors such as success in work, love for work, and recognition in the workplace significantly contribute to predicting performance effectiveness. However, the notable absence of a significant influence from diligence on performance effectiveness suggests that other factors may play a more prominent role in determining the overall effectiveness of administrative personnel in the district.